2(x-3)-3(x+5) = 3(x-2)-7
4 answers
I will be happy to critique your work.
2(x-3) - 3(x+5) = 3(x-2)-7
2x - 6 - 3x + 15 = 3x - 6 - 7
2x - 6 + 6 - 3x +15 + 6 = 3x - 6 - 7
2x - 3x + 22 = 3x - 7
2x + 22 = -7
Now I am stuck
2x - 6 - 3x + 15 = 3x - 6 - 7
2x - 6 + 6 - 3x +15 + 6 = 3x - 6 - 7
2x - 3x + 22 = 3x - 7
2x + 22 = -7
Now I am stuck
I see a problem with your second line. When you distributed the -3 into (x+5), you forgot your negative: (-3)(5) = -15.
2(x-3) - 3(x+5) = 3(x-2) -7
(2x-6) - 3x+-15 = (3x-6) -7
-x-21 = 3x-13
-x-3x = -13+21
-4x = 8
x = 8/-4
x = -2
Is this correct?
(2x-6) - 3x+-15 = (3x-6) -7
-x-21 = 3x-13
-x-3x = -13+21
-4x = 8
x = 8/-4
x = -2
Is this correct?